2002
DOI: 10.1159/000052833
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Single Fallers and Recurrent Fallers among Hospital In-Patients

Abstract: Background: Recurrent fallers constitute a minority of patients who fall but contribute considerably to the total number of falls recorded. Objective: To study the characteristics of recurrent fallers in a hospital setting. Methods: In a prospective observational study we investigated the characteristics of 1,025 patients admitted to a geriatric non-acute hospital. Patients were followed until discharge and were classified as non-fallers, single fallers or recurrent fallers. Results: We identified 824 non-fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 15 publications
5
48
0
Order By: Relevance
“…Similarly to previous investigations fallers presented a prolonged LOS and a greater prevalence of nursing home placement after hospital discharge, with a worsened quality of life for the patients and an increased health care cost burden (Vassallo et al, 2002).…”
Section: Discussionsupporting
confidence: 63%
“…Similarly to previous investigations fallers presented a prolonged LOS and a greater prevalence of nursing home placement after hospital discharge, with a worsened quality of life for the patients and an increased health care cost burden (Vassallo et al, 2002).…”
Section: Discussionsupporting
confidence: 63%
“…Among 270 fallers 46% of them were recurrent fallers. It has been indicated that recurrent fallers might show poor improvement of BI or ADL compared to single and nonfallers [28,29]. However, we attached importance to the first fall to be involved in the present assessment sheet because, as our results clarified, many falls occurred within a short time after admission and because the previous report revealed that fallers might develop a psychological change such as fear of falling resulting in self-induced restrictions in activity [16,17].…”
Section: Discussionmentioning
confidence: 82%
“…These results are in agreement with previous studies that found that the rate of incidence of subsequent falls increased with the number of falls in community-dwelling [16] and hospitalized elderly subjects [17] . Although the risk factors for multiple fallers can be slightly different from one-time fallers [18] , in hospitalized population a signifi cant role seems to be played by the use of CNS active drugs [19] . Our study confi rms these reports, as we found a signifi cant increased risk of falls in subjects treated with neuroleptics and benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%